2023
DOI: 10.3390/ijerph20042773
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant-Emitted Monoterpenes on Anxiety Symptoms: A Propensity-Matched Observational Cohort Study

Abstract: Immersive experiences in green areas, particularly in forests, have long been known to produce beneficial effects for human health. However, the exact determinants and mechanisms leading to healthy outcomes remain to be elucidated. The purpose of this observational cohort study was to investigate whether inhaling plant-emitted biogenic volatile compounds, namely monoterpenes (MTs), can produce specific effects on anxiety symptoms. Data from 505 subjects participating in 39 structured forest therapy sessions at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…Two cohort studies meeting the inclusion criteria involved 547 participants (minimum: 42; maximum: 505; median: 273.5) [36,37]. In both of these studies, the outcomes assessed comprised the composition of the forest air and either physiological or psychological measures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two cohort studies meeting the inclusion criteria involved 547 participants (minimum: 42; maximum: 505; median: 273.5) [36,37]. In both of these studies, the outcomes assessed comprised the composition of the forest air and either physiological or psychological measures.…”
Section: Resultsmentioning
confidence: 99%
“…Each type of forest, including those blanketed in snow, provides a unique setting that could enhance our understanding of the therapeutic effects associated with nature experiences. Despite the current challenges in establishing clear connections between specific forest environments and psychophysiological health benefits, preliminary findings suggest that forests composed of holm oak or a mix of holm oak and pine-common in Mediterranean regions-show promising health outcomes [26,27,34,36]. Furthermore, there is some evidence to suggest that mature and ancient forests may offer greater therapeutic benefits than their younger counterparts, though this assertion is based on a single study [18].…”
Section: Forest Characteristicsmentioning
confidence: 95%
See 1 more Smart Citation
“…In a recent Italian study of forest therapy, exposure to high concentrations of monoterpenes in the air relieved anxiety. 43 Urban green environments also provide favorable cardiovascular effects. 44 Data from Belgium have indicated that urban green spaces may protect against suicide mortality.…”
Section: Diagnosis Of Nature Deficiencymentioning
confidence: 99%
“…A growing number of studies have highlighted the significant impact of a natural environment, particularly forestry, on people's psychophysical well-being. As a matter of fact, forest exposure is associated with beneficial effects at both the physiological [1][2][3][4] and psychological levels [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%